Optimalisasi Peran Mahasiswa dalam Meningkatkan Kualitas Pendidikan Al-Qur’an sebagai Upaya Pemberdayaan Masyarakat di Kelurahan Tangkahan - Andriani, Andriani; Yuris, Evicenna (Journal of Community Sustainability, 2025)
Qur’anic education plays an important role in shaping character and improving the religious quality of the community. The Community Service Program (KKN) conducted in Kelurahan Tangkahan, Medan Labuhan District, Medan City, aims to enhance the quality of Qur’anic education while empowering the local community. The methods used include teaching Qur’an reading, tahfizh guidance, tahsin coaching, as well as interactive educational activities such as games and ice breaking. The program involved various community groups, especially children and mothers, through several Qur’anic education institutions in the area. The results showed an improvement in the ability to read and memorize the Qur’an, as well as an increase in motivation and religious awareness among the community. Challenges faced during implementation were overcome through communicative and participatory approaches. Thus, this KKN program successfully optimized the role of students in empowering the community through Qur’anic education, which is expected to be sustainable and have a positive impact on religious development in Kelurahan Tangkahan.